Extramedullary Hematopoiesis Identified in Pleural Fluid of a Patient with Bilateral Pleural Effusions and Associated Myelofibrosis. (9th November 2022) - Marshall, C; Liu, Y
Abstract: Introduction/Objective: Extramedullary hematopoiesis (EMH) is the formation of blood cells outside of the bone marrow medullary spaces. EMH is typically seen in the spleen or liver and in association with bone marrow replacement disorders, hemoglobinopathies, and other hematological disorders. Rarely EMH can occur in the pleural cavity of patients resulting in subsequent pleural effusions. These cases can accurately be diagnosed with identification of megakaryocytes and other hematopoietic elements in the pleural fluid. Methods/Case Report: We present a 67 year old male with a past medical history of pericardial effusion, Jak 2 positive Myelofibrosis (Post PV/ET), and type II diabetes mellitus, who presented with complaint of shortness of breath for 10 days. The patient did not require oxygen at home and denied any cough or hemoptysis. In the emergency department a Chest X ray was ordered which showed bilateral pulmonary effusions. These effusions were attributed to worsening congestive heart failure, and diuretic therapy was started. With no resolution of the pleural effusions, the decision was made to conduct a thoracentesis and remove the fluid. Interventional radiology then performed a thoracentesis removing 1000 mL from each the left and right pleural spaces. Cytological preparation of the fluid demonstrated myeloid and erythroid precursors as well as occasional megakaryocytes. The diagnosis of extramedullary hematopoiesis was made and the effusion did not recur. Results (if a Case Study enter NA): NA. Conclusion: Extramedullary hematopoiesis of the pleural space is rare. However it must be considered in the differential diagnosis of a patient with persistent effusions and concomitant bone marrow replacement disease such as myelofibrosis. Prompt removal and cytological evaluation of the pleura fluid for hematopoietic elements should be performed in order to diagnose and manage the patient most effectively.